Examining Students’ Speaking Skill Through Youtube Videos: Pre-Experimental Design Study - Dwi Nuraini Wulandari; Wilujeng Asih Purwani (Chalim Journal of Teaching and Learning (CJoTL), 2021)
The aims of this research was to examine the using of youtube videos on students speaking skill. The researcher used the pre experimental design study, which is applied in one group class that get the pre test, treatment, and post test. Youtube videos that used for teaching media of this reasearch, and did the asking and answering question strategy to get the data of this research. Then, the data were analyzed through quantitative procedure. Based on the result of this research showed that teaching students’ speaking skill through youtube videos can improved students’ speaking skill.